PROSPECTS FOR THE DEVELOPMENT OF COMPETITION IN THE HIGHER EDUCATION SYSTEM (Academicia Globe: Inderscience Research, 2023)
The article describes the methods of calculating the efficiency coefficient for improving the skills of employees. Also, models of organization of higher education services at different stages of development of the labor market and a proposal for a "three-phase" mechanism of higher education service provision were developed.